Dynamic and structure of lowland dipterocarps forest after fire in Bukit Suharto, East kalimantan, Indonesia - Ruchaemi, A. (2001)
Approximately 3.5 million ha of lowland forest in Indonesia was heavily burnt in 1982 due to forest fire associated ENSO. This catastrophe were reoccurred heavily in 1998 cause severe damaged of 1.5 million ha forest area. Meanwhile, 520,000 ha were destroyed included those in Bukit Suharto Education Forest covering no less than 4205 ha. It was about 21% of total area. This research reported the impact of forest fire on forest dynamic after 4 years. The research plots was conducted in lowland dipterocarps forest after fire of 9 ha experiment plots. Research plots categorized into 3 subplots of Light Felling (LF) plots (dbh > 50 cm), Heavy Felling (HF) with dbh > 30 cm and control. The result showed that average tree density/ha after prescribed fire were 13.9%, 20.9%, and 29.1% in LF, HF and control respectively. Mean while the diameter distribution of the stand were changed. Considering this severe damage, forest recovery toward normal (climax) stand would take longer time, so that rehabilitation is compulsorily important.